Apis mellifera africanized queens tolerant to the neonicotinoid thiamethoxam - Pizzaia, W. C. S.; Pereira, N. C.; Diniz, T. O.; Toledo, V. A. A.; Ruvolo-Takasusuki, M. C. C. (Scientific Electronic Archives, 2021)
Interaction between bees and plants ensured success in cross-pollination crops, increasing the vigor of the species, as the production of fruits and seeds. Bees are the main pollinators of angiosperms and several crops. Among the factors related to the disappearance of bees in agricultural areas is the excessive or improper use of insecticides. However, agriculture is extremely dependent on pesticides for pest control and the neonicotinoid thiamethoxam is one of the most used insecticides. The use of these chemicals affects the pollinating bee Apis mellifera. Thus, the aim of the study was to select Africanized A. mellifera queens tolerant to thiamethoxam, producing four generations of bees kept in chronic contamination and perform tests to validate tolerance. Colonies of A. mellifera were subjected to chronic contamination by contact with thiamethoxam at a sublethal concentration of 1.65 mg a.i./L. From the surviving colonies, four generations of new queens were produced, kept in chronic contamination with thiamethoxam. Chronic contamination caused changes in the workers’ behavior for 25 days. Validation of selection and tolerance was performed in vitro bioassays to verify mortality and critical electrolyte concentration (CEC). In vitro bioassays showed that there was low mortality after contamination for 24 hours by contact with thiamethoxam at 82.5 mg a.i / L. The analyzes of CEC indicate that there was an increase in gene expression in brain cells, probably as an attempt to detoxify the workers’ organism by contamination with thiamethoxam. New tests need to be carried out with colonies tolerant to the neonicotinoid thiamethoxam, but these initial results indicate that these queens have potential to tolerate this neonicotinoid.